Fast Food Industry Investigation: The Role of Brand Attitude and Brand Loyalty on Purchase Intentions in Generation Z based on Theory of Reasoned Action - Muhammad Taufikkur Rahman Afandi; Endy Gunanto Marsasi (Universitas Muhammadiyah Jakarta, 2023)
This study explores the concepts of brand attitude and brand loyalty among generation z to generate purchase intention in the fast food restaurant industry. Researchers use quantitative methods and use surveys to obtain primary data. The data obtained were then processed using SPSS and AMOS. The total respondents collected in this study were 204 generation Z people who consumed products at fast food restaurants. Variables used in this study include brand attitude, purchase intention, electronic word of mouth, and brand loyalty. The brand loyalty variable in this study will act as a renewal variable mediating between the electronic word of mouth and purchase intention variables. The results of this study show that electronic word of mouth positively affects brand attitude variable but has no effect on brand loyalty variable. Brand attitude variable has a significant impact on brand loyalty variable and purchase intention variable. Brand loyalty variable has a significant effect on purchase intention variable. These findings align with the theory of reasoned action, which states attitude that appears in a person will affect the intention shown in him. The gap in this study is brand attitude because there are differences in previous studies.